2013
DOI: 10.5812/ircmj.16615
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Breast Density in Iranian Women and its Association with Breast Cancer Risk Factors

Abstract: Background:Breast cancer is one of the most common cancers and the first-leading cause of cancer deaths among women in the world. Indeed, breast cancer is ranked as the first malignancy among Iranian women. Breast density, defined as the percentage of fibro glandular breast tissue in mammographic images, is one of the known risk factors for breast cancer. According to American college of radiology-Breast Imaging Reporting and Data System (ACR-BIRADS), mammographic density is divided into four categories. Studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
4
14
0
Order By: Relevance
“…Moreover, high breast density was more frequent in Vietnamese women than low breast density (BI-RADS 1%-8.3%, BI-RADS 2%-19.9%, BI-RADS 3%-43.2%, BI-RADS 4%-28.6%). This could be explained by the fact that Asian women’s breasts are known to be more dense than those of westernized women [ 17 ]; therefore, there can be a high degree of density even in non-cancer women when compared with normalized figures from other countries, and the difference between the number of cancer and normal cases in high breast density groups might not be as substantial as in a Caucasian population. Another possible reason is that the cases in this study were retrieved from both screening and diagnostic populations in oncology hospitals, while other studies have often obtained their data from mammographic screening services.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high breast density was more frequent in Vietnamese women than low breast density (BI-RADS 1%-8.3%, BI-RADS 2%-19.9%, BI-RADS 3%-43.2%, BI-RADS 4%-28.6%). This could be explained by the fact that Asian women’s breasts are known to be more dense than those of westernized women [ 17 ]; therefore, there can be a high degree of density even in non-cancer women when compared with normalized figures from other countries, and the difference between the number of cancer and normal cases in high breast density groups might not be as substantial as in a Caucasian population. Another possible reason is that the cases in this study were retrieved from both screening and diagnostic populations in oncology hospitals, while other studies have often obtained their data from mammographic screening services.…”
Section: Discussionmentioning
confidence: 99%
“…The IFN-γ level may be increased by the diet, resulting in long-term pressure of high IFN-γ levels in some individuals. During lactation, mammary epithelial cells have a strong metabolism, the lobules of the mammary glands expand and the tissue density is increased; thus, mammary glands have an increased risk of pathogenesis ( Ahmadinejad et al, 2013 ). In the present study, the free amino acid analysis showed that IFN-γ treatment resulted in a rapid decrease in the intracellular free arginine concentration and also induced autophagy in primary BMECs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been done to explain the association of breastfeeding and parity with breast cancer [4,[24][25][26][27][28][29][30][31][32][33][34][35][36]. For instance, Dall et al [33] found that parity in younger pregnancies decreases breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%